AI-Driven Discovery of Syringic Acid as an Anthelmintic Agent: Integrating PySCF-Based DFT, Molecular Dynamics, and In Vitro Validation Targeting β-Tubulin : AI-Driven Discovery of Syringic Acid as Anthelmintic agent - Makari, Hanumanthappa; D S N B K, Prasanth; Pasala, Praveen Kumar; Yaraguppi, Deepak A; Anusha, Tummala; Borra, Haindavi; Kanamarlapudi, Lakshmi Chandana; Tallapaka, Esritha (Iranian Journal of Pharmaceutical Sciences, 2026)
Helminthiasis is a global health issue that is particularly prevalent in developing countries. Current anthelmintic drugs, mainly benzimidazoles, have side effects and are resistant to parasites. This study investigated the anthelmintic activity of syringic acid (SYR), a natural polyphenolic compound, against Pheretima posthuma, which targets β-tubulin, using both in silico and in vitro approaches. Drug likeness and ADME/T showed that SYR has a better pharmacokinetic profile than albendazole (ALB). Density functional theory calculations provided insight into the electronic properties and reactivity of SYR and ALB. Molecular docking studies revealed that SYR has a strong binding affinity (ΔG = -6.3 kcal/mol) for β-tubulin, similar to that of ALB (ΔG = -7.2 kcal/mol). Molecular dynamics simulations confirmed the stable binding of SYR in the β-tubulin active site for 100 ns. An in vitro anthelmintic assay on Pheretima posthuma demonstrated that SYR exhibits dose-dependent activity in inducing paralysis and mortality, but is less potent than ALB. The consistency between the computational predictions and empirical bioactivity assays provided preliminary evidence that SYR is a genuine anthelmintic agent. However, further in vivo studies are needed to evaluate the pharmacodynamics, safety, and immunological effects of SYR in complex biological systems before clinical trials. This study provides a basis for the development of new, safer, and more effective anthelmintic agents that target β-tubulin, addressing the problems associated with drug resistance and the side effects of current treatments.